Advanced biosensor technology for mycotoxin detection - Tong, Xinya; Chen, Ning; Wang, Mengzhi; Guo, Xiaodong (Frontiers in Nutrition, 2025)
The increasing incidence of food safety related to mycotoxin contamination highlights a significant global challenge. Traditional mycotoxin detection methods, such as enzyme-linked immunosorbent assay (ELISA) and chromatographic techniques (e.g., high-performance liquid chromatography, HPLC), are often limited by prolonged analysis time, inadequate sensitivity, high costs, and operational complexity, which impede their practical application. In contrast, biosensor technology, possesses interdisciplinary advancements, has emerged as a key area of research due to its inherent advantages, including high sensitivity, rapid response, and cost-effectiveness. This review provides a comprehensive summary of recent technological advancements in the development of highly sensitive biosensors for mycotoxin detection. Furthermore, we propose that future developments should strategically incorporate artificial intelligence (AI), sustainable nanomaterials, and other innovative approaches to enhance biosensor performance significantly and expand their practical applicability in ensuring food safety.